(untitled) (Progressive Agriculture, 2013)
Experiments were carried out in the Field Laboratory of Entomology, Bangladesh Agricultural University, Mymensingh, during February to May, 2008 to investigate the population abundance and to determine the efficacy of three botanical oils (Neem, Mahogani, Karanja) and one synthetic insecticide (Admire 200 SL) against Okra Jassid, Amrasca devastans. The Jassid was first noticed in early March just 7 days after germination and attacked the crop seriously. The highest mean number of Jassid leaf-1 (34) was found in April, 2008. In evaluating the effectiveness of the insecticide and botanical oils to control Okra Jassid, three times applications were made at 7 days interval. The Jassid population varied significantly with the application of insecticide and botanicals. Admire 200 SL give the best result among the treatment. Out of three botanicals Karanja repelled 93.33%, where as Mahogoni and Neem repelled 86.66 and 63.33%.The effectivity of botanicals and synthetic insecticides was found in the following order: Admire 200 SL> Karajan oil >Mahogani oil >Neem oil. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16743 Progress. Agric. 21(1 & 2): 1 7, 2010